Late prehistoric fortifications in Europe defensive, symbolic and territorial aspects from the Chalcolithic to the Iron Age: Proceedings of the International Colloquium 'FortMetalAges', Guimarães, Portugal - Delfino, Davide 1976-; Coimbra, Fernando 1956-; Cruz, Gonçalo; Cardoso, Daniela ca. 20./21. Jh (Archaeopress, 2020)
Late Prehistoric Fortifications in Europe: Defensive, Symbolic and Territorial Aspects from the Chalcolithic to the Iron Age' presents the contributions to the International Colloquium 'FortMetalAges' (10th-12th November 2017, Guimarães, Portugal), The Colloquium was organised by the Scientific Commission 'Metal Ages in Europe' of the International Union of Prehistoric and Protohistoric Sciences (UISPP/ IUSPP) and by the Martin Sarmento Society of Guimaraes. 0Nineteen papers discuss different interpretive ideas for defensive structures whose construction had necessitated large investment, present new case studies, and conduct comparative analysis between different regions and chronological periods from the Chalcolithic to the Iron Age
Keywords: Vor- und Frühgeschichte; Bronzezeit; Eisenzeit; Oppidum; Archäologie; Befestigung; Europa; Heuneburg; Ettenheim-Wallburg; Fortifications, Prehistoric / Europe / Congresses; Excavations (Archaeology) / Europe / Congresses; Excavations (Archaeology); Europe; Conference papers and proceedings; Konferenzschrift -- FortMetalAges -- 2017 -- Guimarães